Burnout in Irish teachers: Investigating the role of individual differences, work environment and coping factors. (August 2015) - Foley, Conor; Murphy, Mike
Abstract: The purpose of the current study is to examine the relative contributions of individual difference, work environment and coping factors to teacher burnout in an integrative predictive model. The study is situated in the Irish context, where no previous such research has been carried out. A cross-sectional survey-based study with a sample of 192 second level teachers was conducted. Results suggest that individual difference, environmental and coping factors to a lesser extent play a significant role in predicting burnout. Each dimension was predicted by varied combinations of these factors, suggesting the need for a broad-based approach to tackling burnout. Highlights: We explore the role of personality, work environment and coping in teacher burnout. Burnout significantly predicted by a combination of these variables. Assertions of the transactional model partially supported by findings. The importance of including each variable type in future studies underlined.